Under the radar. (December 2015) - Mansfield-Devine, Steve
Abstract : Traditionally, Distributed Denial of Service (DDoS) attacks have been used in precisely the manner the name suggests – rendering servers inoperable by overloading them in some way. But the nature of DDoS is changing: increasingly, attackers are leaving just enough bandwidth to enable them to carry out other forms of attack, often with the aim of stealing data. In this interview, Dave Larson, COO of Corero Network Security, explains how DDoS is changing, what the bad guys are up to and how it's now possible to implement effective countermeasures at the periphery of your networks.